Unraveling Tradition: Women’s Place in Pakistan’s Modern Knitting Landscape - Atifa Azad; Aiman Ali Syed; Humaira Zulfiqar; Rafia Syed (International Journal of Contemporary Issues in Social Sciences, 2024)
The culture of knitting addresses knitting as art, craft, design, fashion, and performance, and as an important aspect of everyday life. However, daily activities such as knitting can frequently provide valuable insights about society, culture, and people’s lives. The purpose of this research was to discover the diverse culture of knitting and to understand people’s perspectives regarding this art form. It also finds out how knitters have kept this art alive across different cultures of Pakistan. Furthermore, it explores the factors influencing respondents’ preferences to revamp the art of knitting in this contemporary world. Qualitative research methods including in-depth interviews have been used to profoundly understand the views of respondents. The present study has been conducted at Gulzar Valley, Chakri Road Rawalpindi. The sample was collected through a purposive sampling technique. The findings suggested that as a traditional art knitting is practiced almost in every culture of Pakistan and every culture has different meanings that are attached to this traditional art. The results of this study found that modern knitting culture is perceived differently. The number of young women who knit has increased intensely in the past ten years but their perception of this art has now changed with the aspect of entrepreneurship. The learning practices, creativity, and social aspects have appeared in new ways. The study is essential for young knitters since it is one of the few attempts to comprehend and define their culture. Media also plays a key role in making this art more beneficial in many ways and also in promoting this art worldwide.